The Effectiveness of the Community Service Program (KKN) in Improving the Quality of Islamic Religious Education in Dusun III Helvetia - Alfin Fernando; Ellisa Fitri Tanjung (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the effectiveness of the Community Service Program (KKN) in improving the quality of Islamic Religious Education (PAI) in Dusun III Helvetia. As a form of student community engagement, the KKN program plays a strategic role in providing religious education, character development, and community empowerment through teaching activities, training, and religious mentoring. This research employed a qualitative approach using observation, interviews, and documentation techniques. The findings indicate that the KKN program has a positive impact on enhancing the community’s religious literacy, particularly in aspects of worship understanding, moral strengthening, and community participation in religious activities. Moreover, the involvement of students as learning facilitators fosters a more innovative and interactive educational atmosphere. Thus, the KKN program is proven effective in improving the quality of Islamic Religious Education in Dusun III Helvetia and can serve as a model for community guidance in other areas.